Torajan Local Wisdom-Based Instruction in Teaching Cross-Cultural Understanding - Elim Trika Sudarsi; Syarifuddin Dollah; Murni Mahmud (Indonesian Journal Publisher, 2025)
This study investigates the integration of Torajan local wisdom into instruction to enhance students’ cross-cultural understanding. Using a descriptive qualitative approach, cultural practices such as Rambu Solo’, Rambu Tuka’, Tongkonan symbolism, and proverbs were embedded into teaching strategies. Data were analyzed to examine the effectiveness of these integrations in fostering intercultural competence. The findings indicate that incorporating Torajan local wisdom strengthens cultural identity, enhances intercultural communicative competence, and promotes empathy and respect for diversity. Effective pedagogical strategies include comparative cultural analysis, project-based learning, role-play, and reflective discussion. However, challenges remain, including the risk of cultural misinterpretation and teachers’ limited cultural literacy. The study concludes that embedding indigenous knowledge in classroom practices supports culturally responsive pedagogy and contributes to preparing globally competent learners